Assessing HIV/AIDS stigma and discrimination in developing countries - Becky L. Genberg (2018)
HIV/AIDS-related stigma and discrimination are barriers to HIV prevention effectiveness, voluntary counseling and testing uptake, and accessing care in many international settings. Most published stigma scales are not comprehensive and have been primarily tested in developed countries. We sought to draw on existing literature to develop a scale with strong psychometric properties that could easily be used in developing countries. From 82 compiled questions, we tested a 50-item scale which yielded 3 dimensions with 22 items in pilot testing in rural northern Thailand (n = 200) and urban and peri-urban Zimbabwe (n = 221). The three factors (shame, blame and social isolation; perceived discrimination; equity) had high internal consistency reliability and good divergent validity in both research settings. Systematic and significant differences in stigmatizing attitudes were found across countries, with few differences by age or sex noted within sites. This short, comprehensive and standardized measure can be easily incorporated into questionnaires in international research settings. © 2007 Springer Science+Business Media, LLC.